Minimal Wave Speed in an Integrodifference System of Predator-Prey Type - Baoju Sun; Fuzhen Wu (Discrete Dynamics in Nature and Society)
This article studies the minimal wave speed of traveling wave solutions in an integrodifference predator-prey system that does not have the comparison principle. By constructing generalized upper and lower solutions and utilizing the theory of asymptotic spreading, we show the minimal wave speed of traveling wave solutions modeling the invasion process of two species by presenting the existence and nonexistence of nonconstant traveling wave solutions with any wave speeds.